2009
DOI: 10.1002/app.29965
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of water‐soluble hyperbranched poly(ester)s from maleic anhydride and glycerol

Abstract: A water-soluble hyperbranched polyester with a considerable number of hydroxyl terminal groups was synthesized by reacting maleic anhydride and glycerol in the absence of a solvent. The synthesized intermediate product was converted to the hyperbranched polyester by condensation polymerization, and the water by-product produced during the esterification reaction may be removed by vacuum distillation. In the synthesis process, the crosslinking reaction occurs readily if maleic anhydride is in excess. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…They have been widely used in many fields. [6][7][8] Using hyperbranched polymers as templates to synthesize metal nanoparticles is attracting more and more attentions in recent years. Sun et al [9] synthesized silver nanoparticles using methoxycarbonyl-terminated hyperbranched poly (amine-ester) as templates; Mahapatra and Karak [10] synthesized silver nanoparticle in DMSO solution in the presence of hyperbranched polyamine; and Sun et al [11] researched the effects of hyperbranched poly(amido-amine)s generation number on synthesis of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used in many fields. [6][7][8] Using hyperbranched polymers as templates to synthesize metal nanoparticles is attracting more and more attentions in recent years. Sun et al [9] synthesized silver nanoparticles using methoxycarbonyl-terminated hyperbranched poly (amine-ester) as templates; Mahapatra and Karak [10] synthesized silver nanoparticle in DMSO solution in the presence of hyperbranched polyamine; and Sun et al [11] researched the effects of hyperbranched poly(amido-amine)s generation number on synthesis of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…GPC analysis also revealed that a dramatic effect upon the molecular weight of the HBPs had occurred during the end‐capping procedures (Table and Supporting Information Figs. 9 and 10, GPC traces)—the high PDIs (>20) of acid‐terminated 7a and 7b (PDI values of this magnitude have been reported for hyperbranched polyesters) were reduced to below 3.5 postend‐capping with citronellol.…”
Section: Resultsmentioning
confidence: 66%
“…The preparation of hydroxyesters or hydroxyacids from glycerol and their polycondensation by transesterifi cation has been the subject of recent studies aimed at preparing biodegradable hyperbranched polycarbonates [29] and polyesters [30,31] . Although hyperbranched polyglycerols (Figure 1.11 ) have not thus far been synthesized directly from glycerol, much work has been devoted to their preparation, because of their interesting properties, including biocompatibility, biodegradability, water solubility and aptitude to easy functionalization.…”
Section: Glycerol and Monomers Derived Therefrommentioning
confidence: 99%